A case of malignant atrophic papulosis with cranial nerve and peripheral nerve impairment - Liu,Fang (2015)
Abstract Malignant atrophic papulosisis is a rare, multisystem obliterative vasculopathy of unknown etiology, occasionally involving the cranial nerve. We describe the first case of malignant atrophic papulosisis with cranial nerve and peripheral nerve involvement in China. A 47-year-old woman presented to our hospital with atrophic porcelain white papules over the trunk and extremities, numbness in the right calf, vision decrease and impaired movement of the right eye. She was diagnosed with malignant atrophic papulosisis, based on characteristic symptoms and histopathologic examination. The patient was treated with dipyridamole and aspirin for 9 months, but later died of gastrointestinal hemorrhage. We reviewed currently available case reports on cranial nerve involvement in malignant atrophic papulosisis and emphasized the importance of skin biopsy in diagnosing this disease.